Cellular parameters of the shoot apical meristem in Arabidopsis. - Laufs, P (1998)
The shoot apical meristem (SAM) is a small group of dividing cells that generate all of the aerial parts of the plant. With the goal of providing a framework for the analysis of Arabidopsis meristems at the cellular level, we performed a detailed morphometric study of actively growing inflorescence apices of the Landsberg erecta and Wassilewskija ecotypes. For this purpose, cell size, spatial distribution of mitotic cells, and the mitotic index were determined in a series of optical sections made with a confocal laser scanning microscope. The results allowed us to identify zones within the inflorescence SAM with different cell proliferation rates. In particular, we were able to define a central area that was four to six cells wide and had a low mitotic index. We used this technique to compare the meristem of the wild type with the enlarged meristems of two mutants, clavata3-1 (clv3-1) and mgoun2 (mgo2). One of the proposed functions of the CLV genes is to limit cell division rates in the center of the meristem. Our data allowed us to reject this hypothesis, because the mitotic index was reduced in the inflorescence meristem of the clv3-1 mutant. We also observed a large zone of slowly dividing cells in meristems of clv3-1 seedlings. This zone was not detectable in the wild type. These results suggest that the central area is increased in size in the mutant meristem, which is in line with the hypothesis that the CLV3 gene is necessary for the transition of cells from the central to the peripheral zone. Genetic and microscopic analyses suggest that mgo2 is impaired in the production of primordia, and we previously proposed that the increased size of the mgo2 meristem could be due to an accumulation of cells at the periphery. Our morphometric analysis showed that mgo2 meristems, in contrast to those of clv3-1, have an enlarged periphery with high cell proliferation rates. This confirms that clv3-1 and mgo2 lead to meristem overgrowth by affecting different aspects of meristem function.